Antibacterial activities of SM-1652 compared with those of other broad-spectrum cephalosporins. - Kato, M (1982)
The in vitro and in vivo activities of Sm-1652 were compared with those of other cephalosporins. SM-1652 possessed a wide antibacterial spectrum which included activity against Pseudomonas aeruginosa. It also exhibited potent antibacterial activities against gram-positive cocci and clinical isolates of glucose nonfermentative bacteria. Most notably, its activity against glucose nonfermentative bacteria was the highest of all of the drugs tested. The bactericidal activity of SM-1652 was compared with that of cefoperazone. The difference between the minimum bactericidal concentration and the minimum inhibitory concentration of SM-1652 was actually smaller than that of cefoperazone for Escherichia coli and clinical isolates of indole-positive Proteus spp. SM-1652 was stable for most cephalosporinases but was hydrolyzed to some extent by penicillinases. The in vivo therapeutic effect of SM-1652 against infections in mice was better than those of cefazolin and cefoxitin. The in vivo antipseudomonal activity of SM-1652 was second to that of cefsulodin.